2017
DOI: 10.12963/csd.17380
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship among Nonword Repetition, Age, Vocabulary and Articulation Ability

Abstract: We want to thank Dr. Min Jung Kim for her suggestions on the scoring systems of word test and nonword repetition test and her comments on drafts of this manuscript. Objectives: This study aims to investigate developmental patterns of nonword repetition scores in 3-to 5-year-old typically developing children and examine whether and to what extent nonword repetition scores are related to age, vocabulary and articulatory skills. Methods: A total of 141 children (3-year age group, 37; 4-year age group, 52; 5-year … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
1
1
0
2
Order By: Relevance
“…As parents' behaviors and attitudes can influence children's personality and adjustment to their environment (Johnson, 2006), authoritative parenting might contribute to the development of greater effortful control, which in turn benefits vocabulary skills. Phonological working memory, as measured by the NWR task (Yim & Han, 2019), was positively associated with children's expressive vocabulary skills, which is consistent with previous studies examining these variables (Gathercole et al, 1997;Jung & Ha, 2017). Furthermore, there was a significant negative correlation between children's expressive vocabulary skills and surgency, which suggests that high activity level hinders children's vocabulary development.…”
Section: Internal and External Predictors Of Korean And Englishsupporting
confidence: 86%
See 1 more Smart Citation
“…As parents' behaviors and attitudes can influence children's personality and adjustment to their environment (Johnson, 2006), authoritative parenting might contribute to the development of greater effortful control, which in turn benefits vocabulary skills. Phonological working memory, as measured by the NWR task (Yim & Han, 2019), was positively associated with children's expressive vocabulary skills, which is consistent with previous studies examining these variables (Gathercole et al, 1997;Jung & Ha, 2017). Furthermore, there was a significant negative correlation between children's expressive vocabulary skills and surgency, which suggests that high activity level hinders children's vocabulary development.…”
Section: Internal and External Predictors Of Korean And Englishsupporting
confidence: 86%
“…Phonological working memory is a critical ability that helps children acquire new words (Baddeley, Gathercole, & Papagno, 1998). Many studies have revealed the relationship between phonological working memory and vocabulary skills in both monolingual children (Gathercole & Baddeley, 1989;Gathercole, Hitch, & Martin, 1997;Gathercole, Willis, Emslie, & Baddeley, 1992;Jung & Ha, 2017;Yang & Yim, 2018;Yang, Yim, Kim, & Han, 2013) and bilingual children (Paradis, 2011;Pham & Tipton, 2018;Yim, Jo, Han, & Seong, 2016). Yang and Yim (2018) reported a significant correlation between accuracy on the NWR and receptive vocabulary skills in five to six-year-old monolingual children.…”
mentioning
confidence: 99%
“…구어 모방을 살펴본 국내 연구는 주로 무의미 낱말 따라말하기 과제를 통해 일반 아동의 발달적 특성을 살펴보거나 (Ha, 2020a;Hwang, 2015;Hwang & Ha, 2010;Jung & Ha, 2017), 일반 아동의 수행력과 비교하여 언어장애나 말소리장애, 말 늦은 아동의 특성 을 제시하고 있다 (Oh & Yim, 2013;Ha, 2020b;Pi & Ha, 2021) (Hodges et al, 2016;Masur, 1995;Masur & Eichorst, 2002;Roy & Chiat, 2004) (Archibald & Gathercole, 2006;Dollaghan & Campbell, 1998;Gathercole, 2006;Gathercole & Baddeley, 1996). (Ha & Pi, 2016;Kim & Pae, 2005;Pae, 1995;Stoel-Gammon, 1985) (Masur, 1993(Masur, , 1995Masur & Eichorst, 2002).…”
unclassified
“…또한 말 처리 과정 중 어휘 표상(lexical representation)을 거치지 않아 음운 기억 능력을 정확하게 측정할 수 있는 장점이 있다 (Gathercole & Baddeley, 1989). 무의미 낱말 따라 말하기 수행력은 언어발달과정에서 점차 발달하다 3세 경에 비약 적으로 발달하고 이후에도 점진적으로 발달한다 (Gathercole & Baddeley, 1989;Hwang & Ha, 2010;Jung & Ha, 2017 (Wagner & Torgesen, 1987 (Gillon, 2000;Kim, Shin, & Ahn, 2005;Ko & Kim, 2010;Min, Lee, Choi, & Choi, 2015;Rvachew & Grawburg, 2006;). 음운 기억 능력은 주로 무의미 따라말하기 과제를 통해 살펴보았는데 일 반 아동에 비하여 말소리장애 아동의 무의미 따라말하기 수행력 이 낮다는 연구 결과를 보였다 (Lee & Ha, 2018;Lee, Kim, & Hwang, 2018;Lee & Sim, 2003).…”
unclassified